Determinación de la prevalencia de Anemia Ferropénica en varones y niños de la parroquia El Cisne del Cantón Loja - Carrión Delgado, Cristina Lucía (2014)
Anemia is a public health problem that attacks both developed and developing countries. Some of the most related factors to anemia are iron deficiencies, which is one of the most significant reason that is why we have done this study to determine Iron Deficiency Anemia prevalence, in average, men aged 13 years and children between 0-12 years old from El Cisne, a small town ubicated in Loja; We have used laboratory tests such as blood count and ferritin blood, these were used following the corresponding parameters that helped to determine the disease presence in the population.The results of iron deficiency anemia in children was 32.6% and in adult (males) was 15.4%. Iron deficiency anemia in children presents a remarkable problem, while problem in adults is easier to control; this difference takes place because the iron demands are irregular between these two groups. However, the presence of this disease requires better control in iron administration from early life, as well as having a good diet.